Tuning the electronic and magnetic properties of CoZrxNb1−xFeSi alloys for spintronic and thermoelectric applications. Issue 12 (9th March 2021) - Tariq, Saad; Mubarak, Ahmad A.; Hamioud, Farida
Abstract: This ab‐initio investigation presents the effect of substitution of Zr by Nb atom on the structural, electronic, magnetic, and transport properties of the quaternary Heusler CoZrFeSi alloy. The ab‐initio calculations were performed using the exchange‐correlation of the modified Becke‐Johnson potential. Our results predict that the crystalline phase for each of CoZrFeSi and CoNbFeSi alloys is classified as Type‐I. The calculated formation energy value of the Nb‐doped alloys indicates the thermodynamic stability of the alloys and their possible creation. The bulk modulus value predicts that the rigidity increases with increasing the concentration of the Nb substitute atoms in the alloy. The electronic band structure and the density of states indicate a half metallicity of the alloys with metallic and semiconducting behaviors in the spin up and down, respectively. The studied alloys have shown ferromagnetic character with a high magnetic moment value when increasing the Nb content up to 75%. The calculated Seebeck coefficient and the charge carrier concentration as a function of temperature predict that the present alloys prefer the n‐type doping with the ability to switch between hole and electron for transporting the charges through the Fermi level of CoZr1− x Nb x FeSi ( x = 0, 0.25, 0.75, and 1) alloys. However, CoZr0.5 Nb0.5 FeSi alloy prefers electrons as a charge carrier. Due to their determined properties, beneficial applications are predicted for the present alloys, such as magnetic tunnel junctions and spintronic applications. Abstract : The substitution of Zr by Nb atom of the quaternary Heusler CoZrFeSi alloy proved to influence the structural, electronic, magnetic, and transport properties. The high‐calculated power factor relative to relaxation time ( S 2 σ / τ ) value at elevated temperature for the presented compounds predict that these compounds have beneficial thermoelectric applications, such as the use of waste heat in power generators.